Tergiversation of Human Rights, Deciphering the Core of Kirchnerismo - Korstanje, Maximiliano E. (International Journal of Humanities and Social Science Research, 2016)
After the atrocities perpetrated by Nazism over civilian targets during Would War II philosophy contemplated a neologism to express in words, the barbarian-world imagined by Nazi’s Germany. Human rights were formulated to protect the vulnerabilities of ethnic minorities. However, one of the paradoxes of genocides seems to be related to the fact that the same nation-state which should grant the protection of citizenship violated the human rights of peoples. This was what happened in Latin American dictatorships during 76/82 in Argentina, Uruguay and Chile. The National Process of Reorganization which took the power in 1976, exerted a considerable degree of violence over worker unions and political dissidents. Kirchnerismo today continues the discussion of human right violation of that time, but manipulating its nature in favor of the own interests. The dilemma of “desaparecidos” paves the ways for the creation of two contrasting worlds, which is filled by conspiracy theories produced by Kirchnerismo to keep the hegemony.